Managing Uncertainty in Relationship Development Among Dating App Couples: A Phenomenological Study - Joy Christy Rawung; Inri Inggrit Indrayani; Daniel Budiana (Jurnal Spektrum Komunikasi, 2026)
Relationships initiated via dating applications often encounter higher uncertainty than those formed face-to-face. This is due to limited initial information, potential discrepancies between online and real-life personas, and the absence of clear social references. This study examines how couples who met through dating apps manage relationship uncertainty in the lead-up to marriage decisions. Employing a transcendental phenomenology approach, the research explores participants' subjective experiences. Uncertainty Reduction Theory (URT) serves as the primary conceptual framework, complemented by Self-Disclosure within Social Penetration Theory (SPT) as a key communication strategy for uncertainty management. Data was gathered via in-depth interviews with married couples who met through dating applications. Findings indicate that couples employ various uncertainty reduction strategies: passive (observing online behavior), active (seeking third-party information), and interactive (direct communication and gradual self-disclosure). Self-disclosure is crucial for building trust and accelerating the decision to marry, particularly in terms of openness about life values, marital expectations, and past experiences. The results suggest that deeper self-disclosure leads to stronger relationships. This study contributes to the understanding of interpersonal communication in digital contexts, enhancing our understanding of communication dynamics from online interactions to committed relationships. Practical implications offer valuable insights for dating app users to foster healthier and more meaningful relationships.